Cambios curriculares y pedagógicos en programas de la Facultad de Ingeniería y la reforma de fondo organizacional - Betancourt Uscátegui, Álvaro (Ingeniería, 2003)
The engineering curriculum and particularly the engineering that prepares in fundamental principles that respond to and create technological changes with integral vision are required at present and for the foreseen future. This paper intends a depth modification to the undergraduate programs of engineering in our faculty and particularly for the electronic engineering.